2013
DOI: 10.3892/ol.2013.1176
|View full text |Cite
|
Sign up to set email alerts
|

The role of pro-inflammatory cytokines and immune cells in colorectal carcinoma progression

Abstract: Cytokines exhibit a pleiotropic effect in the regulation of the immune cell function, tumor growth and antitumor immune responses. A total of 30 patients with colorectal carcinoma were enrolled on this study and their levels of interleukin (IL)-1β, IL-6, IL-8, tumor necrosis factor (TNF)-α, serum granulocyte colony-stimulating factor (sG-CSF) and serum macrophage colony-stimulating factor (sM-CSF) were measured preoperatively using ELISA. Tumor-infiltrating granulocyte (TIG), tumor-associated macrophage (TAM),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 28 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…Is it possible that the elevated neutrophil counts in cancer patients are actually the consequence of a more advanced stage, and therefore predict an apparent poorer prognosis? This was acknowledged by Liu et al [178], who showed that the NLR was significantly associated with a more advanced colorectal tumor stage. Also Ietomi [382] observed that the NLR was higher in Stage IV stomach cancer patients than those having stage I-III stomach cancer.…”
Section: Prognostic Values Of Neutrophils and Other Myeloid Subtypes mentioning
confidence: 94%
See 3 more Smart Citations
“…Is it possible that the elevated neutrophil counts in cancer patients are actually the consequence of a more advanced stage, and therefore predict an apparent poorer prognosis? This was acknowledged by Liu et al [178], who showed that the NLR was significantly associated with a more advanced colorectal tumor stage. Also Ietomi [382] observed that the NLR was higher in Stage IV stomach cancer patients than those having stage I-III stomach cancer.…”
Section: Prognostic Values Of Neutrophils and Other Myeloid Subtypes mentioning
confidence: 94%
“…G-CSF was associated with a deeper tumor invasion and a more advanced tumor stage [178]. The granulocyte/lymphocyte ratio was associated with abnormal levels of G-CSF (more than 50 % of the cancer patients) and TIGs were a risk factor for lymph node metastasis in colorectal carcinoma [178].…”
Section: Prognostic Values Of Neutrophils and Other Myeloid Subtypes mentioning
confidence: 96%
See 2 more Smart Citations
“…[13][14][15] A recent study also reported CSF1 expression in more than half (56.7%) of patients with colorectal cancer. 16 The above observations suggest that CSF1 intervention would be a feasible strategy for macrophage-related immune therapy against colon cancer. However, despite of the well-acknowledged correlations between CSF1 level and number of macrophages, there are still debates about the roles of CSF1 in cancer development.…”
Section: Introductionmentioning
confidence: 93%